The Theatre of Naomi Wallace - Cummings, Scott T. author. aut Link
XVI, 320 p. 16 illus.
Keywords: Naomi Wallace, an American playwright based in Britain, is one of the more original and provocative voices in contemporary theatre. Her poetic, erotically-charged, and politically engaged plays have been seen in London's West End, off-Broadway, at the Comédie-Française, in regional and provincial theaters, and on college campuses around the world. Known for their intimate, sensual encounters examining the relationship between identity and power, Wallace's works have attracted a wide range of theatre practitioners, including such important directors as Dominic Dromgoole, Ron Daniels, Jo Bonney, and Kwame Kwei-Armah. Drawing on scholars, activists, historians, and theatre artists in the United States, Canada, Britain, and the Middle East, this anthology of essays presents a comprehensive overview of Wallace's body of work that will be of use to theatre practitioners, students, scholars, and educators alike.